The Impact of Acetic Acid Treatments on Stored Onion (Allium cepa L.) Seeds’ Quality - Hanna Dorna; Agnieszka Rosińska; Dorota Szopińska (Agriculture, 2023)
The aim of the studies was to evaluate the effects of acetic acid treatments on the quality of stored onion seeds. Seeds of two samples were soaked for 30 min in 0.25, 0.5, 1 and 2% acetic acid solutions. Controls included untreated seeds, seeds soaked in distilled water and seeds treated with fungicide Zaprawa Nasienna T 75 WS/DS (a.i. 75% thiram). Germination, vigour and health of untreated and treated seeds were evaluated before and after 2, 6 and 12 months of storage at 4 and 20 °C. Treating onion seeds with acetic acid solutions, especially at the concentrations of 1 and 2%, reduced their infestation with Alternaria alternata, Botrytis cinerea, Cladosporium spp., Penicillium spp. and Stemphylium botryosum after storage at both temperatures. Seeds stored at 20 °C showed lower infestation with fungi than seeds stored at 4 °C. The acetic acid treatments did not have any adverse effect on germination and vigour of stored onion seeds. In some cases, the increase in germination at the first and final counts and the improvement in mean germination time were observed.